Preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel
By loading selenium nanoparticles in bacterial cellulose to form a composite antibacterial hydrogel, the problem of chronic wound infection is solved, and effective antibacterial and wound healing is achieved.
Patent Information
- Application Number
- CN202411348234.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-25
AI Technical Summary
Chronic wounds are easily infected by bacteria during the healing process, leading to the formation of biofilms and prolonged inflammatory stages, which in turn delays wound healing. In the prior art, the antibacterial mechanism of metal nanoparticles has potential toxicity to normal cells, and bacterial cellulose lacks antibacterial ability.
Bacterial cellulose is used as the substrate to load selenium nanoparticles in its internal structure, and the redox reaction of ascorbic acid and selenite acid is used to generate selenium nanoparticles to form a composite antibacterial hydrogel of bacterial cellulose and nanoselenium. Gelatin, as a capping agent and stabilizer, improves the stability and biocompatibility of selenium nanoparticles.
This method provides a multifunctional composite hydrogel that combines antibacterial and promotes wound repair, which can effectively inhibit bacterial growth, provide a moist healing environment, and the selective toxicity of selenium nanoparticles makes it not damage normal cells during the antibacterial process.
Smart Images

Figure CN119499432A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wound dressing preparation, and specifically relates to a preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel. Background Art
[0002] Wound healing is a relatively complex biological process. It is generally divided into four periods, including the hemostatic period (the first day after wound formation), the inflammatory period (the third to fourth day after wound formation), the proliferation period (the fourth to the 14th day after wound formation), and the maturation period (the eighth to the 365th day after wound formation). The four stages of wound repair are not completely independent, and there is some overlap in the time of each stage. Wounds that cannot heal after one month and cannot achieve anatomical structure and functional integrity are generally considered to be chronic wounds, such as diabetic ulcers, pressure injuries, and venous stasis ulcers. More than 70% of chronic wounds are susceptible to bacterial infection during the healing process. When chronic wounds are superimposed with infection, treatment often fails. One of the main reasons for the failure of treatment of chronic wound infection is the formation of biofilms. Bacteria attach to the wound through specific interactions between anchoring proteins and the villi on the surface of the wound, produce biofilm matrix, and form dense microcolonies. The microcolonies further mature to form microbial biofilms. In the normal healing process, wounds proceed in an orderly manner. In chronic wounds, a prolonged inflammatory phase increases the time it takes for wounds to heal. Biofilms promote this inflammation and thus delay wound healing by constantly interacting with components of the host immune system, including neutrophils, macrophages, and inflammatory cytokines. Therefore, antimicrobial agents are particularly important in the process of diabetic wound repair. Due to the increasing resistance of bacteria to antibiotics, metal nanoparticles (such as silver, gold, copper, and titanium) have become a commonly used antimicrobial strategy. The antimicrobial mechanism of metal nanoparticles is mainly membrane damage and toxicity caused by biophysical interactions between nanoparticles and bacteria. However, once metal ions enter normal cells, they can access and bind to all proteins, enzymes, and other biomolecules in the cell. This may cause loss of catalytic activity, changes in function, DNA mutations, chain breaks, or gene regulation.
[0003] As a trace element in the human body, selenium is an essential nutrient for the human body. The normal selenium level in an adult is about 10-20 mg, and the dietary requirement is about 40 μg (the maximum daily limit is 300 μg). In recent years, zero-valent nano-selenium particles have a wide range of application prospects in biomedicine due to their good biological activity, low toxicity, anti-cancer, antioxidant properties and good antibacterial effects. Compared with nano-silver, selenium nanoparticles not only have effective antibacterial effects on a variety of bacteria including drug-resistant bacteria, but also show selective toxicity to bacteria, so that they do not damage normal body cells while being antibacterial. In addition, selenium is a key element of many antioxidant enzymes and functional proteins, and it plays an important role in the homeostasis of oxidative stress. Studies have shown that compared with sodium selenite, selenomethionine and selenomethylselenocysteine, nano-selenium can better induce the synthesis of glutathione peroxidase (GPx) and thioredoxin reductase (TRx), thereby having high antioxidant activity, and can effectively prevent oxidative damage to DNA.
[0004] Wound dressings should have the function of promoting wound healing while being antibacterial. In recent years, bacterial cellulose hydrogels have great application prospects in the biomedical field, especially in wound dressings, due to their high mechanical strength, porosity, hydrophilicity, good biocompatibility and simple preparation. Bacterial cellulose is a natural polymer hydrogel produced and secreted by microorganisms such as Acetobacter, Rhizobium, and Agrobacterium. The water content can be as high as 70%-95%, which can provide a moist healing environment for wounds, promote the growth of granulation tissue and absorb tissue exudate, etc. However, most chronic wounds are easily infected by bacteria during the healing process, and bacterial cellulose does not have antibacterial ability. However, its unique three-dimensional network structure can load antibacterial substances to make up for this defect. Therefore, combining bacterial cellulose and antibacterial substances will be an ideal antibacterial solution.
[0005] In summary, this scheme uses bacterial cellulose with high porosity, water content and good biocompatibility as the substrate, utilizes the reducing property of ascorbic acid, loads selenium nanoparticles in the internal structure of bacterial cellulose, and designs a multifunctional composite hydrogel that has both antibacterial properties and promotes wound repair. Summary of the invention
[0006] In view of the problems raised by the above background technology, the purpose of the present invention is to provide a preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel,
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0008] The preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel include the following steps:
[0009] Step 1: comprising a selenious acid solution and a gelatin solution, dissolving selenious acid in the gelatin solution, and adding an ascorbic acid solution to the selenious acid solution to undergo an oxidation-reduction reaction to generate selenium nanoparticles;
[0010] Step 2: Add bacterial cellulose to the solution of step 1 and fully soak it for at least 3 hours to obtain a bacterial cellulose and nano-selenium composite antibacterial hydrogel.
[0011] It is further defined that the mass fraction of gelatin in the gelatin solution in step one is 0.5 wt %.
[0012] It is further defined that the concentrations of the selenious acid solution in step 1 are 20 mM, 30 mM and 40 mM respectively.
[0013] It is further defined that in the step 1, the molar ratio of the ascorbic acid to the selenious acid is 2:1, the reaction temperature in the step 1 is 25° C., and the reaction time is 30 min.
[0014] It is further defined that the size of the bacterial cellulose in step 2 is prepared into discs using a puncher with a diameter of 16 mm and a puncher with a diameter of 6.5 mm respectively.
[0015] It is further defined that the bacterial cellulose in step 2 can be squeezed to remove moisture from the bacterial cellulose before being added to the solution in step 1.
[0016] The preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel provided by the present invention have at least the following beneficial effects compared with the prior art:
[0017] 1. The bacterial cellulose gel used in the present invention has good mechanical properties, which makes the dressing not easy to be damaged. When used, it can fit tightly to the wound, effectively absorb tissue exudate from the wound, and provide a moist healing environment for the wound.
[0018] 2. The present invention uses gelatin as a capping agent and stabilizer for preparing selenium nanoparticles, which greatly improves the stability and biocompatibility of selenium nanoparticles.
[0019] 3. In the present invention, selenium nanoparticles can be uniformly dispersed in bacterial cellulose, which helps to solve the problem of sudden release of selenium nanoparticles in the material.
[0020] 4. In summary, the preparation method provided by the present invention is simple to operate, low in cost, and has universal applicability, and is easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention can be further illustrated by the non-limiting examples given in the accompanying drawings;
[0022] Figure 1 It is a preparation method and a preparation method step diagram of an application example of the bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0023] Figure 2 The scanning electron microscope image of the preparation method and application example of the bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0024] Figure 3 The transmission electron microscope image of selenium nanoparticles in the preparation method and application example of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0025] Figure 4 The Raman characteristic spectrum diagram of the preparation method and application example of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0026] Figure 5 The ultraviolet-visible-near-infrared spectroscopic diagram of the preparation method and application example of the bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0027] Figure 6 The Fourier transform infrared absorption spectrum of the preparation method and application example of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0028] Figure 7 The thermogravimetric curve of the preparation method and application example of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0029] Figure 8 A hydrogel plate colony diagram of the preparation method and application example of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention;
[0030] Fig. 9 This is a statistical chart of the antibacterial rate of the hydrogel according to the preparation method and application example of the bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0032] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0033] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Bacterial cellulose is a widely used natural polymer material. A large number of studies have applied it to wound dressings. Selenium nanoparticles have also been found to be a human micronutrient with antibacterial, anticancer, low toxicity and good biocompatibility. At present, there have been studies combining the two to form antibacterial hydrogels for use in wound healing. This study used selenious acid and hydrazine hydrate to undergo redox reactions to generate selenium nanoparticles to play an antibacterial role, and explored the optimal antibacterial concentration. Given that hydrazine hydrate is highly toxic, hydrazine content above 10 ppb can induce fatty degeneration, nausea, pulmonary edema, nasal irritation, DNA damage and temporary blindness. This study replaced hydrazine hydrate with non-toxic ascorbic acid and explored the optimal antibacterial concentration.
[0035] like Figure 1-Figure 9 As shown, the preparation method and application of bacterial cellulose and nano-selenium composite antibacterial hydrogel of the present invention include the following steps:
[0036] Step 1: comprising a selenious acid solution and a gelatin solution, dissolving selenious acid in the gelatin solution, and adding an ascorbic acid solution to the selenious acid solution to undergo an oxidation-reduction reaction to generate selenium nanoparticles;
[0037] Specifically, in this step, ascorbic acid, as one of the basic exogenous vitamins, is known for its powerful antioxidant and anti-inflammatory properties. Ascorbic acid is a polyhydroxy compound whose center is formed by a five-membered carbon ring. Ascorbic acid has strong reducing properties due to the presence of double bonds on the C2 and C3 carbons and the presence of four hydroxyl groups at the C2, C3, C5 and C6 positions. It has good biocompatibility compared to the reducing agent hydrazine monohydrate. Selenium is the main structural component of many enzymes and plays an important role in many functions of the body and tumor prevention. Selenium toxicity may be produced through certain mechanisms, such as oxidative stress or selenium replacing sulfur during protein assembly, but these selenium toxicities depend on its form. Selenium alone shows better bioavailability and lower toxicity than other forms of selenium. Selenium nanoparticles have attracted attention due to their very small size and antibacterial properties. Due to their very small size, there are more opportunities to interact with bacteria per unit area, which can make the antibacterial activity of selenium nanoparticles more powerful. Selenium nanoparticles kill bacteria by destroying their membranes and releasing their intracellular components, making it difficult for them to develop drug resistance.
[0038] Step 2: Add bacterial cellulose to the solution of step 1 and fully soak it for at least 3 hours to obtain a composite hydrogel of bacterial cellulose and selenium nanoparticles.
[0039] Specifically, in this step, bacterial cellulose is obtained through the secretion of Acetobacter xylinum by static culture, a fermentation medium of Acetobacter xylinum is prepared, Acetobacter xylinum is cultured in the fermentation medium, and static culture is carried out in a biochemical incubator for one week, a layer of bacterial cellulose hydrogel film is formed on the surface of the culture medium, the bacterial cellulose hydrogel film is taken out, washed twice with sodium hydroxide solution, and then washed three times by boiling with ultrapure water to obtain a purified bacterial cellulose hydrogel.
[0040] In this step, bacterial cellulose and selenium nanoparticles composite hydrogel is a diabetic wound dressing; bacterial cellulose is a pure natural polymer hydrogel with good biocompatibility, high water retention, high purity and non-immunogenicity. It can provide a moist healing environment for the wound, absorb wound exudate and promote the growth of granulation tissue. At the same time, its unique three-dimensional network structure can load selenium nanoparticles to enable them to be continuously and slowly released at the wound site to achieve a long-term antibacterial effect. Selenium is a trace element in the human body. Zero-valent nano-selenium particles have good biological activity and low toxicity, anti-cancer, antioxidant properties and good antibacterial effects. As an antibacterial agent, it will not cause bacteria to develop drug resistance. When selenium nanoparticles are composited with bacterial cellulose, the purpose of antibacterial and promoting wound repair can be achieved.
[0041] Preferably, the mass fraction of gelatin in the gelatin solution in step one is 0.5 wt %.
[0042] Preferably, the concentrations of the selenious acid solution in step 1 are 20 mM, 30 mM and 40 mM respectively.
[0043] Preferably, in the step 1, the molar ratio of the ascorbic acid to the selenious acid is 2:1, the reaction temperature in the step 1 is 25° C., and the reaction time is 30 min.
[0044] Preferably, the bacterial cellulose in step 2 is prepared into discs using a puncher with a diameter of 16 mm and a puncher with a diameter of 6.5 mm, respectively.
[0045] Preferably, the bacterial cellulose in step 2 can be squeezed to remove moisture from the bacterial cellulose before being added to the solution in step 1.
[0046] The preparation method of the bacterial cellulose and selenium nanoparticle composite hydrogel is described in detail below in conjunction with specific preferred embodiments.
[0047] Embodiment 1:
[0048] 1. Preparation of selenium nanoparticles:
[0049] S11: Number the beaker containing 100g of sterile water as No. 1, prepare a gelatin solution with a mass fraction of 0.5wt%, add it to four beakers (beakers No. 2-5), add 100g to each beaker, numbered 2-5, accurately weigh 0.258g, 0.387g, and 0.516g of selenious acid, respectively, and dissolve them in the 0.5wt% gelatin solution in beakers No. 3-5. Dissolve them fully to obtain precursor selenious acid mother solutions with concentrations of 20mM, 30mM, and 40mM, respectively.
[0050] S12: Place beakers 1-5 on a magnetic stirrer, set the speed of the magnetic stirrer to 400 r / min, add ascorbic acid to beakers 3-5 at a molar ratio of 2:1, and then reduce selenious acid to selenium nanoparticles through the reaction 2C6H8O6(aq)+H2SeO3(aq)=3H2O+Se↓+2C6H6O6(aq), wherein beakers 1 and 2 are not treated with any reagents, the reaction temperature is 25°C, and the reaction time is 5 min.
[0051] 2. Preparation of bacterial cellulose:
[0052] S21: Prepare the fermentation medium of Gluconacetobacter xylinum: Use a balance to accurately weigh 20g of glucose, 5g of peptone, 6.8g of disodium hydrogen phosphate dodecahydrate, 5g of yeast extract powder, 1.5g of sodium citrate and 1000g of water. Then divide it into conical bottles and put it into an ultrasonic cleaner for ultrasonic oscillation until the solute is evenly dispersed, and then put it into a high-pressure sterilizer for sterilization at 121°C for 20min. When the temperature of the high-temperature and high-pressure steam sterilizer drops to 80°C, take it out and place it on a clean bench in a sterile environment to cool for use.
[0053] S22: Activation and inoculation of bacterial cellulose: Take out the bacterial solution of Acetobacter xylinum stored in a refrigerator at a temperature of 4°C, inoculate it into a sterile culture medium at a ratio of 10%, and culture it for two days to enhance the activity of the bacteria. Then use it as the mother solution and inoculate it into other culture media at a concentration of 10%, and culture it for 3-5 days to obtain bacterial cellulose.
[0054] S23: Purification of bacterial cellulose: Take out the bacterial cellulose in the conical flask, discard the culture medium, add ultrapure water to rinse repeatedly, then add it to an aqueous solution containing 4% sodium hydroxide and boil it for 1 hour to sterilize and remove bacteria and other impurities. Then soak it in ultrapure water and replace it every day for one week until the pH value of the whole system reaches neutral, that is, pH = 7.
[0055] S24: Cutting the size of bacterial cellulose: Use a 24-well plate puncher (diameter 16 mm) and a 96-well plate puncher (diameter 6.5 mm) to prepare appropriate amounts of discs for later use.
[0056] 3. Preparation of bacterial cellulose and selenium nanoparticles composite hydrogel:
[0057] S31: Add bacterial cellulose discs with a diameter of 16 mm into sterile water, 0.5 wt% gelatin solution, and selenious acid / gelatin solutions of different concentrations, respectively, and fully soak for 3 hours.
[0058] S32: Take out the hydrogels in the five beakers, add sterile water to rinse for multiple times, and remove the excess chemicals to obtain bacterial cellulose, bacterial cellulose / gelatin, bacterial cellulose / gelatin / nano-selenium-20, bacterial cellulose / gelatin / nano-selenium-30, and bacterial cellulose / gelatin / nano-selenium-40.
[0059] Embodiment 2:
[0060] In addition, the morphology of bacterial cellulose and selenium nanoparticles composite hydrogel was observed, such as Figure 2 As shown:
[0061] The prepared hydrogel was placed in a -20℃ refrigerator for 12 hours, and then placed in a freeze dryer for 48 hours to remove the water in the hydrogel. The dried sample was fixed to one side of the stage with a conductive adhesive and sprayed with platinum for 300 seconds under maximum vacuum to improve the conductivity of the sample, which is more conducive to imaging. Finally, the morphology of these samples was characterized by a scanning electron microscope at a voltage of 10KV.
[0062] Regarding the transmission electron microscopy characterization of selenium nanoparticles, Figure 3 As shown:
[0063] This study adopts the drop method to prepare the characterization sample. The solution obtained in S12 of Example 1 is taken out, the filter paper is placed in a culture dish, the copper support membrane is placed on the filter paper with the front side facing up, a small amount of solution is sucked with a 200μL pipette, the pipette is vertically suspended above the copper support membrane, and the pipette handle is gently pushed to make the solution slowly drip onto the copper support membrane, dripping 2-3 drops, and the prepared sample is placed in a vacuum drying oven set at 40°C and left to dry for 12 hours. Finally, the diameter size of the prepared selenium nanoparticles is characterized.
[0064] Regarding the Raman spectral characterization of bacterial cellulose and selenium nanoparticles composite hydrogel, Figure 4 As shown:
[0065] The Raman test was used to determine whether the selenium nanoparticles in the bacterial cellulose and selenium nanoparticle composite hydrogel sample showed a unique Raman band position in the spectrum to determine whether it was successfully synthesized. The sample preparation method was consistent with the preparation steps of the freeze-dried sample in the morphology observation of Example 2. The freeze-dried sample was placed in a laser confocal Raman spectrometer and scanned at a wavelength of 1064nm. -1 -4000cm -1 Scanning is performed to obtain the Raman characteristic spectrum of the hydrogel.
[0066] Regarding the UV-visible-near-infrared spectrophotometric characterization of bacterial cellulose and selenium nanoparticles composite hydrogel, e.g. Figure 5 As shown:
[0067] The selenium nanoparticles in the bacterial cellulose and selenium nanoparticle composite hydrogel sample were characterized by UV-visible near-infrared spectrophotometer. The sample preparation method was freeze-drying, which was consistent with the freeze-dried sample in the morphology observation of Example 2. The UV-visible near-infrared spectrophotometer of the composite hydrogel was obtained by scanning in the wavelength range of 200nm-800nm.
[0068] Regarding the Fourier transform infrared absorption spectroscopy characterization of bacterial cellulose and selenium nanoparticles composite hydrogel, Figure 6 As shown:
[0069] The characteristic functional groups of the bacterial cellulose and selenium nanoparticle composite hydrogel samples were analyzed by Fourier transform infrared absorption spectrometry. The sample preparation method was consistent with the freeze-dried sample in the morphology observation of Example 2. The test range was from 400 cm -1 -4000cm -1 , where the resolution is 5cm -1 .
[0070] Regarding the thermal stability characterization of bacterial cellulose and selenium nanoparticles composite hydrogel, Figure 7 As shown:
[0071] The stability of the bacterial cellulose and selenium nanoparticle composite hydrogel sample was evaluated by its thermal gravimetric curve. The sample preparation method was consistent with the freeze-dried sample in the morphology observation in Example 2. A nitrogen atmosphere was used as the test condition. The temperature rise gradient in the system was 10°C per minute, and the test temperature range was 30°C-600°C.
[0072] Regarding the antibacterial properties test of bacterial cellulose and selenium nanoparticles composite hydrogel, Figure 8 , Fig. 9 As shown:
[0073] In this study, the antibacterial ability of bacterial cellulose and selenium nanoparticles composite hydrogel against Gram-negative bacteria (such as Escherichia coli) and Gram-positive bacteria (such as Staphylococcus aureus) was evaluated by colony counting method.
[0074] (1) Preparation method of MH broth liquid culture medium
[0075] Accurately weigh MH broth culture medium powder reagent according to the standard of 21g / L, add it to a conical flask filled with a certain amount of ultrapure water, put the conical flask into an ultrasonic cleaner for ultrasonic oscillation, so that the culture medium powder can be evenly dispersed. After it is evenly dispersed, heat it to dissolve, seal the dissolved culture medium with a bacteria filter membrane, put it into a high-temperature and high-pressure steam sterilizer at 121℃ for 0.5h to sterilize, take it out when the temperature indicator of the sterilizer shows that the temperature drops to 80℃, transfer it to an ultra-clean workbench to cool, and set it aside.
[0076] (2) Preparation method of MH broth solid culture medium
[0077] Accurately weigh the MH broth medium powder reagent according to the standard of 21g / L, and accurately weigh the agar powder reagent according to the standard of 20g / L, add the above two reagents into a conical flask filled with a certain amount of ultrapure water, put the conical flask into an ultrasonic cleaner for ultrasonic oscillation, so that the medium powder and agar can be evenly dispersed. After uniform dispersion, heat and boil until the agar is completely dissolved, seal the dissolved MH broth medium with a filter membrane, put it into a high-temperature and high-pressure steam sterilizer at 121℃ for 0.5h for sterilization, take it out when the temperature indicator of the sterilizer shows that the temperature drops to 80℃, and immediately transfer it to the clean bench. Before the culture medium cools and solidifies, pour it into a sterile plastic culture dish, cover the entire surface, let it stand and cool for use.
[0078] (3) Bacterial activation and culture
[0079] Activation of bacterial strains: Take out the bacteria cultured with solid culture medium from a 4°C refrigerator and place it on a clean workbench. Burn the inoculation loop with an alcohol lamp and cool it to ensure that there is no contamination from other bacteria. Pick a single colony from the solid culture medium and transfer it to an EP tube containing 3mL of liquid culture medium. Place it in a constant temperature shaker at 200r / min and 37°C. After activation for 2-3h, draw 30μL and transfer it to 3mL of liquid culture medium. Continue to culture it in a constant temperature box under the same conditions. Repeat this operation three times to obtain the bacterial strain used in subsequent experiments.
[0080] Bacterial culture: Take 30 μL of the previously activated bacteria into an EP tube containing 3 mL of liquid culture medium, seal it with a sealing film, and place it in a constant temperature shaker at 200 r / min and 37°C for 8 to 9 hours to make the bacterial concentration in the culture medium reach 10 8 CFU / mL, and obtain the bacterial inoculum stock solution.
[0081] (4) Colony count method (CFU)
[0082] The prepared sample with a diameter of 16 mm and a thickness of about 3 mm was co-cultured with phosphate buffered saline (PBS) for 4-6 h in a 24-well plate to displace the water in the sample and neutralize the pH of the sample. Then, the PBS was aspirated and the sample was cultured to a concentration of 10 8 The bacterial solution was diluted to 10 CFU / mL 6 CFU / mL, 0.5mL was added to each well, and the bacteria and samples were co-cultured in a 37℃ incubator for 12h, and ultrasonically vibrated in an ultrasonic cleaner for 5min to make the bacteria adsorbed on the surface of the sample fall off, and the bacterial suspension was aspirated and diluted with PBS at different times so that the final colony was 10 3CFU / mL, take 100μL of the diluted bacterial solution and evenly spread it on the solid MH broth plate, place the plate in a 37℃ constant temperature incubator and culture for 24h, count the colonies on the plate and take pictures, and calculate according to the antibacterial rate formula, the calculation method can be expressed as follows:
[0083]
[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing a bacterial cellulose and nano-selenium composite antibacterial hydrogel, characterized in that: The steps include: Step 1: comprising a selenious acid solution and a gelatin solution, dissolving selenious acid in the gelatin solution, and adding an ascorbic acid solution to the selenious acid solution to undergo an oxidation-reduction reaction to generate selenium nanoparticles; Step 2: Add bacterial cellulose to the solution of step 1 and fully soak it for at least 3 hours to obtain a composite hydrogel of bacterial cellulose and selenium nanoparticles.
2. The method for preparing the bacterial cellulose and nano-selenium composite antibacterial hydrogel according to claim 1, characterized in that: The mass fraction of gelatin in the gelatin solution in step 1 is 0.5 wt %.
3. The method for preparing the bacterial cellulose and nano-selenium composite antibacterial hydrogel according to claim 1, characterized in that: The concentrations of the selenious acid solution in step 1 are 20 mM, 30 mM and 40 mM respectively.
4. The method for preparing the bacterial cellulose and nano-selenium composite antibacterial hydrogel according to claim 1, characterized in that: In the step 1, the molar ratio of the ascorbic acid to the selenious acid is 2:1, the reaction temperature in the step 1 is 25° C., and the reaction time is 30 min.
5. The method for preparing the bacterial cellulose and nano-selenium composite antibacterial hydrogel according to claim 1, characterized in that: The bacterial cellulose in step 2 is prepared into discs using a puncher with a diameter of 16 mm and a puncher with a diameter of 6.5 mm respectively.
6. The method for preparing the bacterial cellulose and nano-selenium composite antibacterial hydrogel according to claim 1, characterized in that: Before adding the bacterial cellulose in step 2 to the solution in step 1, the water therein can be completely drained by squeezing.
Citation Information
Cited By
Acetobacter xylinum for producing red selenium-rich nano cellulose and application of acetobacter xylinum
CN121427724A
